Efficacy and Safety of Apatinib in Advanced Hepatocellular Carcinoma: A Multicenter Real World Retrospective Study - Zheng, Zhuangzhuang; Liu, Zijing; Zhang, Haifeng; Guo, Xiao; Jia, Xiaojing; Wang, Jianfeng; Meng, Lingbin; Xin, Ying; Jiang, Xin (Frontiers in Pharmacology, 2022)
Background and purpose: Apatinib is a novel antiangiogenic agent that can target vascular endothelial cell growth factor 2. The aim of our study was to evaluate the efficacy and safety of apatinib mesylate in the treatment of advanced hepatocellular carcinoma (HCC) in the real world. Methods: We retrospectively analyzed 178 patients with advanced HCC who had been treated with apatinib mesylate from January 2017 to March 2020. The primary outcome indexes were progression-free survival (PFS) and overall survival (OS), and the secondary outcome indexes were objective response rate (ORR), disease control rate (DCR), and incidence of treatment-related adverse reactions. Results: Univariate analysis showed that patients with third-line treatment (P<0.001), alpha fetoprotein (AFP) ≥400 ng/ml (P<0.05), distant metastasis (P<0.05), portal vein tumor thrombus (PVTT) (P<0.05), and apatinib monotherapy (P<0.001) had shorter survival. Multivariate analysis confirmed that third-line drugs, PVTT, and combination therapy were independent prognostic factors for PFS in all patients. Univariate analysis showed that Eastern Cooperative Oncology Group (ECOG) scores (P<0.05), medication lines (P<0.001), AFP (P<0.001), tumor progression (P<0.05), PVTT (P<0.05), and combination therapy (P<0.001) may impact the OS. Multivariate analysis proved that AFP, PVTT, and combination therapy were independent prognostic factors for OS. The most common adverse reactions were secondary hypertension (29.21%), symptoms of fatigue (16.85%), hand and foot syndrome (16.29%), vomiting (14.04%), liver dysfunction (6.18%), and proteinuria (6.74%). Most of the adverse reactions were Grade 1 or 2. Conclusions: Apatinib mesylate is an effective treatment for advanced HCC, and its adverse reactions are relatively mild. Medication lines, PVTT, AFP level, and combination therapy were independent prognostic factors for patients with advanced HCC who were treated with apatinib.